Enhancing Urban Traffic Flow Through Signal Optimization: A Case Study of Traffic Chowk, Butwal - Sapkota, Aayushma; Singh, Samridhi; Dhungel, Subhash (International Journal on Engineering Technology, 2025)
The continuous growth of urban traffic at intersections creates critical challenges because many cities cannot develop their infrastructure fast enough to accommodate rising vehicle numbers. The research behind this investigation studied Traffic Chowk, Butwal, Nepal to optimize traffic flow and signal timing with the purpose of boosting operational efficiency and reducing vehicle waiting times. A traffic volume study was conducted to analyze vehicle movement patterns and SIDRA Intersection modeling to evaluate intersection performance. This evaluation establishes that most areas at the intersection provide Level of Service C but Purano Buspark faces peak-hour LOS F congestion which requires optimized traffic management along with adaptive signal controls for urban sustainability goals. Smart traffic control systems demonstrate critical importance for developing areas because they reduce congestions while enhancing roadway efficiency.